Crystal structure of a new phenyl(morpholino)- methanethione derivative: 4-[(morpholin-4-yl)- carbothioyl]benzoic acid. - AGNIMONHAN, Finagnon H.; Bendeif, El-Eulmi; AHOUSSI, AKANNI LÉON; GBAGUIDI, Ahokannou Fernand; Martin, Eddy; Wenger, Emmanuel; Lecomte, Claude (My University, 2020)
4-[(Morpholin-4-yl)carbothioyl]benzoic acid, C12H13NO3S, a novel phenyl- (morpholino)methanethione derivative, crystallizes in the monoclinic space group P21/n. The morpholine ring adopts a chair conformation and the carboxylic acid group is bent out slightly from the benzene ring mean plane. The molecular geometry of the carboxylic group is characterized by similar C—O bond lengths [1.266 (2) and 1.268 (2) A ° ] as the carboxylate H atom is disordered over two positions. This molecular arrangement leads to the formation of dimers through strong and centrosymmetric low barrier O—H O hydrogen bonds between the carboxylic groups. In addition to these intermolecular interactions, the crystal packing consists of two different molecular sheets with an angle between their mean planes of 64.4 (2). The cohesion between the different layers is ensured by C—H S and C—H O interactions.
Keywords: crystal structure; phenyl(; morpholino)methanethione